Nano-curcumin: A Potent Enhancer of Body Antioxidant System in Diabetic Mice. - Nitin Dadasaheb Potphode; Jitesh Ankush Daunde; Sneha Sampatrao Desai; Madhuri Vasant Walvekar (International Journal of Phytomedicine, 2018)
Nano preparation of drug to be helpful in targeted delivery, which avoids any unwanted damage of adjacent healthy tissues. Antidiabetic compounds from natural and synthetic sources have been found to successful management of diabetes. Antioxidants are compound that protect cell against the damaging effects of reactive oxygen species (ROS). Curcumin has many beneficial effects against health problems; it has limited use due to its poor bioavailability as concluded by number of its pharmacokinetic studies. Since the aim of this study was to investigate the effects of curcumin nanoparticles (Nano-curcumin) on antioxidative enzymes i.e Glutathione peroxidase (GPx), Superoxide dismutase (SOD) and Catalase (CAT) in pancreas of diabetic mice. For the present investigation mice (Mus musculus) used as experimental animal. Mice were divided into four groups viz, a) Control group b) Diabetic group c) Recovery group I- Diabetic mice treated with curcumin d) Recovery group II - Diabetic mice treated with curcumin and nano-curcumin. The activity of antioxidative enzymes in the pancreas was recorded at the end of experiment. There was decrease in antioxidative enzymes in pancreas of diabetic mice compared to control. After the treatment of curcumin and curcumin nanoparticles significant increase in levels of antioxidative enzymes in recovery group I and II was observed. Moreover as compare to free curcumin nano-curcumin showed better results in enhancement of antioxidative enzymes. Thus it proves that nano-curcumin found to be potent antioxidative compound to reduced oxidative stress induced during the diabetes.